From the “technical” company to the “philosophical” company. Demand of sense for the company. (Journal of Parents and Teachers, 2012)
Resources are made for the proyects and the proyects are made to achieve a good life. Enterprises (and enterprises’ chiefs) had suffered, as almost every single current institutions, a demoralization consequence of its incapacity to develop a coherent function with a purpose. Only recovering the purpose will be posible to find again the subject and then, enterprises will be able to be what they were. Philosophy must guide the enterprises in order to find the sense that is lacking.
Keywords: Resources; Proyects; Social justice; Charity; Love; Friendship; Good life; Enterprise; Enterprise’s chief; Star action; Richness; Economy; experiencies